Trends of Congenital Anomalies in Paediatric Orthopaedic Surgery in Pakistan Emirates Military Hospital Rawalpindi - Orfi, Fayyaz; Udin Hassan, Hassan; Ur Rehman, Hafiz Faiz; Khan, Abdul Manan; Wajid, Muhammad Yaseen; Tariq, Muhammad Umar (Pakistan Armed Forces Medical Journal, 2025)
Objective: To demonstrate the trends regarding the congenital disease burden in the paediatric orthopaedic surgery and explore the importance of enhancing paediatric orthopaedics in Pakistan.Study Design: Retrospective, Cross-Sectional StudyPlace and Duration of Study: Department of Orthopaedic Surgery, Pakistan Emirates Military Hospital Rawalpindi, Pakistan from Jan 2022 to Dec 2024.Methodology: Paediatric patients with age range of 0-12 years, both genders suffering from a congenital disorder with complete medical record of diagnosis and patient information were included in the study. A total of 840 patients who had a complete medical record were included in the study. After the screening through administration, the patient medical profiles in Health Information Management System were accessed. After comprehensive evaluation and assessing the medical files regarding the patients visiting Orthopaedic Surgery Department, the relevant patients’ data was obtained, and data extraction sheets were made. Frequencies and percentages were calculated regarding the type of congenital anomalies.Results: In 2022, 204(24.3%) patients with different congenital anomalies reported to the orthopaedic surgery department. 275 (32.7%) of congenital anomalies were seen in 2023 and increased percentage of 361(42.9%) was demonstrated in 2024 with DDH being most common with 100 patients.Conclusion: Increased number of patients with congenital disorders were seen in the Orthopaedic Surgery Department of PEMH over the last 3 years. Increased frequency of developmental dysplasia of hip being 26.7% and clubfoot being 26.4% were noted, highlighting the need to acknowledge paediatric orthopaedic surgery in Pakistan.